2015
DOI: 10.4314/bajopas.v8i1.23
|View full text |Cite
|
Sign up to set email alerts
|

Dry season prevalence of contagious bovine pleuropneumonia based on postmortem examination at Hadejia Abattoir, Jigawa State

Abstract: The current prevalence study of CBPP was conducted at Hadejia abattoir of Jigawa state, Nigeria using postmortem examination of CBPP lesions in lungs of cattle at slaughter. A total of 172 slaughtered cattle were examined at postmortem over the period of 3 months (March-May, 2014). Of the total, 5(2.9%) were positive for the presence of CBPP lesions. The disease was significantly higher (P<0.05) in females 4(8.3%) than in males 1(1.8%). Cattle within the rage of 3.5-4 years 3(9.7%) were significantly (P<0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…The present study established a prevalence rate of 3.49%. This finding is higher than previous reports; 0.29% (Aliyu et al, 2000) for 1988-1997 for five northern states; 0.13% (Adamu & Aliyu, 2006) for 1988-1997 for Borno state; 0.01% was reported in Zaria, Kaduna state (Alawa et al, 2011) and 2.60% (Gumel et al, 2015) for (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) dry season abattoir prevalence in Jigawa state, all in northern Nigeria. The higher prevalence observed in this study may indicate the endemic nature of the disease, increased and unrestricted cattle movement, porous nature of borders among other factors.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The present study established a prevalence rate of 3.49%. This finding is higher than previous reports; 0.29% (Aliyu et al, 2000) for 1988-1997 for five northern states; 0.13% (Adamu & Aliyu, 2006) for 1988-1997 for Borno state; 0.01% was reported in Zaria, Kaduna state (Alawa et al, 2011) and 2.60% (Gumel et al, 2015) for (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) dry season abattoir prevalence in Jigawa state, all in northern Nigeria. The higher prevalence observed in this study may indicate the endemic nature of the disease, increased and unrestricted cattle movement, porous nature of borders among other factors.…”
Section: Discussioncontrasting
confidence: 59%
“…The finding of this study suggests that CBPP is prevalent in all months of the year in Adamawa state irrespective of the season. This contradicts the findings of Alhaji & Babalobi, (2015) and Gumel et al (2015) who reported higher prevalence during dry season; and also Adamu & Aliyu, (2006) who reported higher prevalence in rainy season. The persistence of CBPP throughout the year is a pointer that much needs to be done about the disease in this part of the country.…”
Section: Discussionmentioning
confidence: 58%
“…Histopathological changes, severity, and score in the different pathogens/interactions. Nigeria is higher than previous reports of 0.29% by Aliyu et al [9] 0.13% by Adamu and Aliyu [10] , 0.21% by Adamu et al, [11] 0.01% by Alawa et al, [12] 2.60% by Gumel et al, [13] and 3.49% by Francis et al [14] There seem to be an increase in the prevalence of bovine pneumonia observed in the last few years in Nigeria, which indicated the need for attention. The 9.68% prevalence of bovine pneumonia observed in Ghana is consistent with the findings of Attoh-Kotoku et a.…”
Section: Discussionmentioning
confidence: 57%
“…The white Fulani breed was observed to be more susceptible in Nigeria, and this is consistent with the findings of Olabode et al [16] that recorded a higher susceptibility of this breed to mycoplasma pneumonia, while the WASH breed was the most susceptible in Ghana, which is also consistent with the findings of Attoh-Kotoku et al [15] Bovine pneumonia is commonplace in cattle herds that are subjected to prolonged period of feed shortages with intercurrent diseases (Trypanosomes) and long-distance grazing which precipitate affected ones into active infection. [13,15] These prevalences further established respiratory system problems, particularly pneumonia, as one of the major health problems in livestock production; this has been associated with significant economic losses and a threat to food security. [17] Histopathological findings showed that bronchopneumonia and bronchointerstitial pneumonia are the most common types of pneumonia present; this further underscores observations of Akpavie et al [18] The nature of the lesions in the lungs from Ghana is predominantly fibrino-necrotic inflammatory type as compared to the more of suppurative and fibrinous types observed in Nigeria which is suggestive of the fact that Mannheimia haemolytica and/or Pasteurella multocida contribute predominantly as causes of bacterial pneumonia in Nigeria and that of Ghana is more to Mycoplasma spp induced pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation